METHYLENETETRAHYDROFOLATE REDUCTASE C677T GENE POLYMORPHISM AND PROSTATE CANCER RISK - Tellouche-bouhouhou, Samah; Chellat-rezgoune, Djalila; Abadi, Noureddine; Satta, Dalila; Dahdouh, Abderrezak (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The single nucleotide polymorphism C677T of the methylenetetrahydrofolate reductase (MTHFR) gene encodes a thermolabile enzyme. This polymorphism was found to be implicated in cancer susceptibility. In this study, we analyzed the distribution of the MTHFR C677T polymorphism in two cohorts; patients and controls native of East of Algeria to explore the possible association between this polymorphism and prostate cancer susceptibility. Methods: Our examination has been conducted in 98 cases and 98 healthy controls. Genotyping was realized by polymerase chain reaction-restriction fragment length polymorphism method. Results: Compared with CC homozygous, the CT heterozygous was found to have a significantly increased risk of prostate cancer (p=0.04; odds ratio [OR]=2.01, 95% confidence interval [CI]: 1.02–3.95). However, no statistically significant difference was observed concerning the TT homozygous (p=0.74; OR=1.25, 95% CI: 0.51–3.04). Conclusion: Our results indicate that the genotype CT is a risk factor for prostate cancer in East of Algeria.